2017
DOI: 10.4067/s0717-73562017005000003
|View full text |Cite
|
Sign up to set email alerts
|

Presencia De Un Centro Ceremonial Formativo en La Circumpuna De Atacama

Abstract: … había una ceremonia de clausura, luego de que una delgada capa de relleno de montículo o arena fuera dispuesta sobre el piso, se procedía a sellar esta superficie, quemando madera y paja (Hastorf 2008a:9).En el presente trabajo se discuten las evidencias del sitio Tulán-54 con especial énfasis en el templete central. Este sitio es parte de un sistema de tres grandes asentamientos formativos tempranos sincrónicos (3450 a 2370 años cal. a.p.), dispuestos en el transecto Tulán, en un tramo de 15 km en el SE de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
45

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 14 publications
(20 reference statements)
0
17
0
45
Order By: Relevance
“…This agrees with analyses using stable carbon and nitrogen isotopes of human bones from Caleta Vitor and other coastal areas which have revealed a longterm pattern of food consumption based primarily on marine resources compared with terrestrial inputs (see also Olguín, 2014;Olguín et al, 2014;Pestle et al, 2015;Salazar et al, 2015 for the arheic coast of northern Chile), despite local environmental fluctuations and socio-cultural changes among inland groups that evolved into Formative (Neolithic) societies, with farming and pastoralism as key socio-economic factors (see Table 1 for regional cultural phases; Núñez and Santoro, 2011;McRostie, 2014;Muñoz et al, 2016;Núñez et al, 2017). A recent study also found that terrestrial animal resources were incorporated into other economic processes of production and consumption in different periods (Valenzuela et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with analyses using stable carbon and nitrogen isotopes of human bones from Caleta Vitor and other coastal areas which have revealed a longterm pattern of food consumption based primarily on marine resources compared with terrestrial inputs (see also Olguín, 2014;Olguín et al, 2014;Pestle et al, 2015;Salazar et al, 2015 for the arheic coast of northern Chile), despite local environmental fluctuations and socio-cultural changes among inland groups that evolved into Formative (Neolithic) societies, with farming and pastoralism as key socio-economic factors (see Table 1 for regional cultural phases; Núñez and Santoro, 2011;McRostie, 2014;Muñoz et al, 2016;Núñez et al, 2017). A recent study also found that terrestrial animal resources were incorporated into other economic processes of production and consumption in different periods (Valenzuela et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Debe notarse que para el lapso 3.800-2.500 a.p. hay registros cerámicos que han sido detectados en distintos sitios de la Puna chilena y argentina (Aschero et al 1999;Fernández 1988Fernández -1989Muscio 2011;Núñez et al 2006Núñez et al , 2017 así como en las tierras bajas del NOA (Ortiz 2003).…”
Section: Discussionunclassified
“…The deposits surrounding the ceremonial centre contain remains of the primary and secondary order, with hearths and dispersed ash deposits, bones, plant and lithic remains dating from 2380 to 3080 bp (non‐cal. dates) (Núñez et al ., ). Three types of camelids – guanacos, vicuñas and llamas – have been identified (Cartajena et al ., ).…”
Section: Puripica‐tulan Tarajne and Tilolacar Phasesmentioning
confidence: 97%